2017
DOI: 10.5489/cuaj.4797
|View full text |Cite
|
Sign up to set email alerts
|

Moses technology in a stone simulator

Abstract: Introduction: The objective of this study was to compare fragmentation efficiency of the conventional regular mode of holmium laser to the Moses contact mode on a stone simulator. Methods: The Lumenis ® Pulse TM P120H holmium laser system together with Moses D/F/L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 12 publications
(19 reference statements)
1
44
0
2
Order By: Relevance
“…Laser fiber diameter, method of cleaving and laser technology also play a part in dusting and pop-dusting, and future studies also need to evaluate this aspect [1618]. The impact of Moses technology in relationship to dusting and pop-dusting is still unclear and perhaps might carry an advantage due to decreased retropulsion, but this aspect needs to be studied further [19].…”
Section: Discussionmentioning
confidence: 99%
“…Laser fiber diameter, method of cleaving and laser technology also play a part in dusting and pop-dusting, and future studies also need to evaluate this aspect [1618]. The impact of Moses technology in relationship to dusting and pop-dusting is still unclear and perhaps might carry an advantage due to decreased retropulsion, but this aspect needs to be studied further [19].…”
Section: Discussionmentioning
confidence: 99%
“…Laser lithotripsy-related complications such as presence of ureteral mucosal injury and perforation were classified according to the modified Clavien grading system and compared between the two groups. 6 Success rate was assessed using low-dose CT scans at 3 months. Success rate was defined as no ureteral fragments or presence of nonobstructive renal fragments of £4 mm.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In addition, Moses mode was associated with significantly lower procedural time and significantly improved stone fragmentation efficiency than the regular mode. 6 However, there are no randomized clinical studies evaluating the effectiveness of this new Moses technology in reducing stone retropulsion and improving procedural and/or fragmentation/pulverization times during ureteroscopic Holmium laser lithotripsy. Therefore, the objective of this clinical trial was to compare regular and Moses modes of Holmium laser lithotripsy in terms of stone retropulsion, stone fragmentation/pulverization time, and procedural time during retrograde ureteroscopy in a double-blinded prospective randomized manner.…”
mentioning
confidence: 99%
“…Pulse duration is one of the parameters we can work on, and long pulse duration was shown to reduce stone pushback in reproducible experimental conditions . Moses technology in holmium:YAG laser has been shown to significantly reduce retropulsion, in both dusting and fragmentation settings . A case series using the Moses technology for lithotripsy has been shown to decrease stone retropulsion in 18 of 23 procedures, with a trend of better fragmentation rate .…”
Section: Ureteroscopy and Retrograde Intrarenal Surgerymentioning
confidence: 99%
“…159,160 Moses technology in holmium:YAG laser has been shown to significantly reduce retropulsion, in both dusting and fragmentation settings. 161,162 A case series using the Moses technology for lithotripsy has been shown to decrease stone retropulsion in 18 of 23 procedures, with a trend of better fragmentation rate. 163 Cost-effectiveness analysis also showed that the decrease in lasing time achieved by the Moses system does not translate into sufficient cost savings to offset the higher cost of the laser fiber and software.…”
Section: Lithotripsymentioning
confidence: 99%